The Effect of Capital Adequacy, Size and Liquidity on the Profitability of Skye bank Nigeria plc - Gbegi, Daniel Orsa; Abubakar, Ibrahim Abubakar (Kashere Journal of Management Sciences, 2024)
This study investigated the effect of capital adequacy and liquidity on the profitability of deposit money banks in Nigeria with particular interest in skye bank Nigeria plc. The study made use of secondary data, obtained from the bank’s annual reports and statements of accounts. Covering a period of 2006-2015, from which return on assets, capital adequacy, liquidity ratios and asset size were computed. Simple linear regression was performed. The Findings revealed that liquidity and capital adequacy have significant and positive effect on the profitability of bank. The study therefore, recommends that subsequent reform of the banking industry should be geared toward maintaining adequate level of liquidity and capital adequacy rate which will in the long run enhance profitability of the banks.